Intrahousehold health care financing strategy and the gender gap: Empirical evidence from India - Abay Asfaw; Stephan Klasen; Francesca Lamanna (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2008)
The 'missing women' dilemma in India has sparked interest in investigating gender discrimination in the provision of health care in the country. No studies, however, have directly examined this discrimination in relation to household behavior in health care financing. We hypothesize that households who face tight budget constraints are more likely to spend their meager resources on hospitalization of boys rather than girls. We use the 60th Indian National Sample Survey and a multinomial logit model to test this hypothesis and to shed some light on this important but overlooked issue. The results reveal that while the gap in the probability of boys' and girls' hospitalization and usage of household income and savings is relatively small, the gender gap in the probability of hospitalization and usage of scarce resources is very high. Ceteris paribus, the probability of boys to be hospitalized by financing from relatively scarce sources such as borrowing, sale of assets, help from friends, etc., is much higher than that of girls. Moreover, the results indicate that the gender gap deepens as we move from the richest to poorest households.
Keywords: I12; O15; J71; 330; gender discrimination; health care finance; hospitalization; India; Geschlechterdiskriminierung; Gesundheitsfinanzierung; Privater Haushalt; Gesundheitsvorsorge; Frauen; Indien